Growth Characterization of Single and Double Salmonella Methionine Auxotroph Strains for Potential Vaccine Use in Poultry - Rubinelli, Peter; Kim, Sun Ae; Park, Si Hong; Baker, C. Adam; Ricke, Steven C. (Frontiers in Veterinary Science, 2017)
Poultry meat is an important source of zoonotic Salmonella infection. Oral vaccination of chickens with live attenuated Salmonella during grow-out is an attractive approach to control of Salmonella colonization in the chicken gastrointestinal tract. In this study, we report the construction of methionine-dependent and growth of Salmonella Typhimurium mutant strains with methionine auxotrophy (∆metR and ∆∆metRmetD) and survival in chicken feed and fecal matrices. The methionine auxotroph mutant ∆∆metRmetD grew slowly on L-methionine but failed to grow on D-methionine, as expected, and exhibited lower affinity for methionine compared to the isogenic parent strain (metR single mutant) in whole-cell affinity experiments. Preliminary data conducted as part of a previously published bird challenge study indicated that the methionine auxotroph was less effective at protection in chickens to a challenge with virulent wildtype parent strain but generated greater Salmonella-specific serum IgG. Although the auxotroph could not sustain itself in minimal media it was able to survive when incubated in the presence of chicken and fecal material. The immune response appears promising but further work may be needed to alter low-affinity methionine transporters and methionine biosynthesis genes in combination with the knock-out of the high affinity transporter metD reported here to ensure timely clearance of the candidate vaccine strain.